Neohydatothrips John species (Thysanoptera: Thripidae) in Nayarit, Mexico, and description of a new species - Valenzuela-García, Rita D.; Retana-Salazar, Axel P.; Johansen-Naime, Roberto M.; García-Martínez, Oswaldo; Gallego-Morales, Gabriel; Carvajal-Cazola, Carlos (Instituto de Ecología, A.C., 2012)
The species of Neohydatothrips from the state of Nayarit, associated to different crops are presented. Also a new species similar to N. mirandai Johansen is described which differs from the rest by having a yellow pronotum.